PENGARUH KUALITAS PELAYANAN, KONSULTASI, PENGAWASAN DAN PEMERIKSAAN PAJAK TERHADAP KEPATUHAN WAJIB PAJAK - Hanan Devana Safitri; Diana Fajarwati (Program Studi Ilmu Administrasi Negara, Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam '45 (UNISMA) Bekasi, 2023)
The This study aims to determine the effect of Service Quality, Consultation, Supervision and Tax Audit on Compliance with Corporate Taxpayers at KPP Pratama Bekasi Utara. The method used in this research is quantitative. The place of this research is at KPP Pratama Bekasi Utara. The data used is primary data. The population in this study are corporate taxpayers who are registered at KPP Pratama Bekasi Utara. The sampling technique in this study was to use a purposive sampling technique, namely taking samples based on certain criteria from the required population. The data search technique is by distributing the questionnaire directly. The data that has been collected is then processed using the SPSS 22 computer program. Based on the statistical test results, the service quality variable has a significant positive effect on taxpayer compliance, the consulting variable has a significant positive effect on taxpayer compliance, the monitoring variable has a significant positive effect on taxpayer compliance, and tax audit variables have no effect and are not significant on taxpayer compliance